Respuesta :
The sum of the terms in a geometric sequence is obtained through the equation below,
S = (a1)(1 - r^n)/(1 - r)
Substituting,
S = 2(1 - 3^7) / ( 1 - 3) = 2186
Thus, the sum of the first 7 terms in the geometric sequence is equal to 2186.
S = (a1)(1 - r^n)/(1 - r)
Substituting,
S = 2(1 - 3^7) / ( 1 - 3) = 2186
Thus, the sum of the first 7 terms in the geometric sequence is equal to 2186.
Answer: The required sum is 2186.
Step-by-step explanation: We are given to find the sum of the following geometric series with 7 terms:
[tex]2+6+~.~.~.~+1458.[/tex]
We know that the sum of a geometric series up to 'n' terms with first term 'a' and common ratio 'r' is given by
[tex]S=\dfrac{a(r^n-1)}{r-1}.[/tex]
In the given geometric series, we have
first term, a = 2
and the common ratio 'r' is
[tex]r=\dfrac{6}{2}=3.[/tex]
Also, n = 7.
Therefore, the sum of the given series is
[tex]S\\\\\\=\dfrac{a(r^n-1)}{r-1}\\\\\\=\dfrac{2(3^7-1)}{3-1}\\\\\\=\dfrac{2(2187-1)}{2}\\\\\\=2186.[/tex]
Thus, the required sum is 2186.